(untitled) (Research, Society and Development, 2023)
Acute calculous cholecystitis is one of the most frequent diseases in emergencies. Annually, approximately 500,000 cholecystectomies are performed in the USA. The female versus male ratio is 4:1 at reproductive age and evens out with aging. Gallstones can obstruct the cystic duct, which can cause gallbladder distension and biliary colic. Prolonged obstruction results in inflammation, infection, and even ischemia, a common condition known as Acute Cholecystitis (AC). The objective of the study is to identify the prevalence of mortality due to acute cholecystitis in the state of Santa Catarina between 2015 and 2021. This is an ecological study of time series of mortality in Santa Catarina. Data will be collected from the Hospital Information System (SIH-SUS), from the Santa Catarina and national population, made available by DATASUS. A total of 14,279 deaths were identified in Brazil, of which 716 (5.01%) were from the state of SC. It is concluded when evaluating the linear regression rates that Brazil presents a predominance of stability, and the state of Santa Catarina demonstrates a profile of stability in relation to all races and an increase behavior in the Great West region. Accordingly, when analyzing the age variable, it is noted that the state of CS presents an increase in the linear regression rates in the EF 40 to 49 years, despite Brazil demonstrating stability in relation to the age group variable.